"SKIN WINDOW" EXUDATE IL-1Β AND IL-18 IN PATIENTS WITH CHRONIC URTICARIA - Загрешенко, Денис Сергеевич; Климов, Владимир Васильевич; Трофименко, Наталья Александровна; Дорофеева, Маргарита Сергеевна (Medicine in Kuzbass, 2022)
Research subject. 26 patients at the age of 18 to 45 years with chronic urticaria were studied. The control group was composed of 25 healthy persons of 20 to 35 age.Research purpose was to pick up a cell-free «skin window» exudate fraction and study its pro-inflammatory cytokine values in chronic urticaria.Methods. The method of «skin window» chamber modified by Klimov V.V. et al. (patent № 1534395 and medical technology ФС № 2010.217) has been used to evaluate cytokine IL-1β and IL-18 values in the skin. The ELISA was exploited to assess cytokine concentrations in exudates, whereas they were previously standardized using the microbiuret approach in relation to the total protein value.Results. At the «shock organ» level, a statistical validity regarding the control increase in pro-inflammatory cytokines IL-1β and IL-18 was revealed in chronic urticaria. It can be a hidden cause behind inflammasomes as multimolecular complexes in many inflammatory cells in the skin.Conclusions. In chronic urticaria, the study of «skin window» exudate pro-inflammatory cytokines is important for such «shock organ» as the skin that enables the assessment of inflammatory activity and may correspond to inflammasome formation.
Keywords: chronic urticaria; cytokines; «skin window»; IL-1β; IL-18